Bevacizumab in HIV-positive patients: concerns about safety and potential for therapeutic use. (August 2014) - Magné, Nicolas; Chargari, Cyrus; Levy, Antonin; Guy, Jean-Baptiste; Merrouche, Yacine; Spano, Jean-Philippe
Abstract : Human immunodeficiency virus (HIV) patients have more aggressive presentation of colorectal cancer (CRC) and less favourable outcome. Bevacizumab is an antiangiogenic agent that has emerged as a major drug for metastatic CRC. However, few data are available on the safety of bevacizumab in HIV patients. In the light of a case study, we briefly draw intention on how angiogenesis inhibitors could interact with antiviral tri-therapy.